The Problem of Negative Interfaces in Stratigraphic Excavations: Two Case Studies from Swat - Olivieri, Luca M. (Ancient Pakistan, 2020)
Old stratigraphic archaeology methods foresee a model where all the layers are sealed and easily recognisable, provided that they are correctly excavated. The presumed integrity of the physical sequence might instead hide gaps that remain unnoticed. Such gaps are the result of negative interventions, which generally did not leave evident traces, but whose existence can be reconstructed ex post. Such gaps, or ‘negative interfaces’, are of paramount importance for the reconstruction of the cultural sequence. The article illustrates these problematics through two cases from the direct fieldwork experience of the author, in two completely different contexts, at the sanctuary of Saidu Sharif I and at the urban site of Barikot, both in Swat.